Surface mass balance and stable oxygen isotope ratios from shallow firn cores on Fimbulisen, East Antarctica - Schlosser, E; Anschütz, Helgard; Isaksson, E.; Martma, T; Divine, Dmitry V; Nøst, O.-A. (Annals of Glaciology, 2012)
Source at https://doi.org/10.3189/2012AoG60A102 . The mass balance of Antarctica is one of the crucial factors for determining sea-level change in a warming climate. The marginal zones of the continent, namely the ice shelves, are most sensitive to climate change. During the 2009/10 austral summer an extensive glaciological field campaign was carried out on Fimbulisen, an ice shelf in East Antarctica, to investigate its recent surface mass balance. Shallow (10–18 m) firn cores were drilled and accumulation rates and stable-isotope ratios determined. For firn-core dating, two different methods were compared: (1) seasonal variations of stable oxygen isotope ratios (δ 18 O), and (2) dielectric profiling, including using the volcanic eruptions of Pinatubo, Philippines (1991), and El Chichόn, Mexico (1982), as time markers. The mean annual accumulation for the period 1992–2009 ranges from 298 to 349 mmw.e. a –1 . The interannual variability at the drilling sites is >30%. Accumulation rates show a weak decreasing trend during the past 20–30 years, which is statistically significant only for one of the cores. Stable-isotope ratios were compared to the snowfall temperature of Neumayer station. Neither the temperatures nor the δ 18 O values show any trend for the investigated time period.